Dynamic Line-Scan Thermography for the Inspection of Paper-Based Materials: A Case Study Focused on an Ancient Book Cover - Hai Zhang; Stefano Sfarra; Clemente Ibarra-Castanedo; Xavier P. V. Maldague (Proceedings, 2019)
This work is focused on the use of line-scan thermography (LST) method for the inspection of an ancient book cover. Three widely used image post-processing techniques (i.e., pulsed phase thermography, partial least square thermography and principal component thermography) were applied to the acquired thermal sequences. Flash thermography (FT) anticipated the LST results in order to have a comparison of the results. It was concluded that LST is an effective technique for paper-based materials, and it can additionally provide a higher image contrast if compared to classical FT technique.